Biodegradable gemcitabine-loaded microdevice with sustained local drug delivery and improved tumor recurrence inhibition abilities for postoperative pancreatic tumor treatment. (31st December 2022) - Kong, Xiangming; Feng, Miao; Wu, Lihuang; He, Yiyan; Mao, Hongli; Gu, Zhongwei
Abstract: At present, the 10-year survival rate of patients with pancreatic cancer is still less than 4%, mainly due to the high cancer recurrence rate caused by incomplete surgery and lack of effective postoperative adjuvant treatment. Systemic chemotherapy remains the only choice for patients after surgery; however, it is accompanied by off-target effects and server systemic toxicity. Herein, we proposed a biodegradable microdevice for local sustained drug delivery and postoperative pancreatic cancer treatment as an alternative and safe option. Biodegradable poly(l -lactic-co-glycolic acid) (P(L)LGA) was developed as the matrix material, gemcitabine hydrochloride (GEM·HCl) was chosen as the therapeutic drug and polyethylene glycol (PEG) was employed as the drug release-controlled regulator. Through adjusting the amount and molecular weight of PEG, the controllable degradation of matrix and the sustained release of GEM·HCl were obtained, thus overcoming the unstable drug release properties of traditional microdevices. The drug release mechanism of microdevice and the regulating action of PEG were studied in detail. More importantly, in the treatment of the postoperative recurrence model of subcutaneous pancreatic tumor in mice, the microdevice showed effective inhibition of postoperative in situ recurrences of pancreatic tumors with excellent biosafety and minimum systemic toxicity. The microdevice developed in this study provides an option for postoperative adjuvant pancreatic treatment, and greatly broadens the application prospects of traditional chemotherapy drugs.